The Props-Based Interface for Neurosurgical Visualization - Hinckley, Ken; Pausch, Randy; Downs, J. Hunter; Proffitt, Dennis; Kassell, Neal F. (MMVR5: Medicine Meets Virtual Reality 5, 1997)
We describe a three-dimensional human-computer interface for neurosurgical visualization. The interface is based on the two-handed physical manipulation of hand-held tools, or "props", in free space. These user interface "props" facilitate transfer of the user's skills for manipulating tools with two hands to the operation of a user interface for visualizing 3D medical images, without need for training. The interface allows neurosurgeons to explore a 3D MRI scan of a patient's brain during presurgical planning. From the surgeon's perspective, the interface is analogous to holding a miniature head in one hand which can be "sliced open" or "pointed to" using a cross-sectioning plane or a stylus tool, respectively, held in the other hand. Cross-sectioning a 3D volume, for example, simply requires the surgeon to hold a plastic plate (held in the preferred hand) up to the miniature head (held in the nonpreferred hand) to demonstrate the desired cross-section.